2023
DOI: 10.1021/acs.jpcc.3c03663
|View full text |Cite
|
Sign up to set email alerts
|

Screening of 225 Double-Transition-Metal o-MXenes for Superior Thermoelectric Property at Room Temperature from First-Principles Electron and Phonon Calculations

Abstract: The high-throughput workflows are developed to efficiently and reliably predict the electrical and thermal conductivities of double-transition-metal o-MXenes. We conduct the calculations for 225 double-transition-metal o-MXenes with different transition-metal combinations, surface terminations (−H, −F, −O, and −OH), and structural types (“212” and “223”). For all investigated o-MXenes, their electrical conductivities are found to be in the range from 105 up to 107 S/m, indicating that o-MXenes are good electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The dominance of F atoms in the phonon spectrum of F-terminated MXenes at the lower frequency has been reported before. 84 The above results indicate that the inter-atomic bonding between F and Mo atoms is much weaker than Mo–O bonds.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The dominance of F atoms in the phonon spectrum of F-terminated MXenes at the lower frequency has been reported before. 84 The above results indicate that the inter-atomic bonding between F and Mo atoms is much weaker than Mo–O bonds.…”
Section: Resultsmentioning
confidence: 83%
“…It is also worth noting that the lattice thermal conductivities obtained for Mo 2 TiC 2 , Mo 2 TiC 2 O 2 and Mo 2 TiC 2 F 2 monolayers using the MTPs are also different to those reported in ref. 84 within the harmonic phonon calculations. Using the MTPs trained for atomic forces and total energies at finite temperatures can partly incorporate higher order anharmonic effects in the renormalized second order and third order inter-atomic force constants, leading to a more reliable description for phonon conduction than that of harmonic approximation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Guha et al 19 investigated MXene transistors with low-resistive contacts and sequentially calculated electronic (such as the bandgap and in-plane static dielectric constant), structural, and thermodynamic properties using DFT. Other studies employing HTCS have successfully identified optimal MXenes by computing various properties, including mechanical properties such as in-plane stiffness, 20 thermoelectric properties such as Seebeck coefficients, 21 and magnetic properties such as ferroelectricity. 22 The ability to accurately identify and screen various properties of MXenes using computational methods is crucial in HTCS, which has made HTCS an invaluable method in MXene research.…”
Section: Introductionmentioning
confidence: 99%